2016
DOI: 10.1016/j.ijsu.2016.06.039
|View full text |Cite
|
Sign up to set email alerts
|

A transanal procedure using TST STARR Plus for the treatment of Obstructed Defecation Syndrome: ‘A mid-term study’

Abstract: The TST STARR Plus is a simple, safe, and effective option for selected patients with ODS. Long-term prospective clinical studies are needed to validate the advantages of this emerging, novel procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In Group C, the success rate results to be higher if compared with the already published data ranging from 83.3 to 88.2% 27 with a considerably lower early and longterm postoperative complications rate. 19,[28][29][30][31] The success rate of Group D is consistent with those reported about excisional surgery, around 95%, 32 with a lower postoperative complications and reoperation rates. [7][8][9] However, despite the published review, some long-term studies showed poor global success rates for all HD treatments, such as 65% for CSH, 9 73% for excisional surgery, and 70% for THD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In Group C, the success rate results to be higher if compared with the already published data ranging from 83.3 to 88.2% 27 with a considerably lower early and longterm postoperative complications rate. 19,[28][29][30][31] The success rate of Group D is consistent with those reported about excisional surgery, around 95%, 32 with a lower postoperative complications and reoperation rates. [7][8][9] However, despite the published review, some long-term studies showed poor global success rates for all HD treatments, such as 65% for CSH, 9 73% for excisional surgery, and 70% for THD.…”
Section: Discussionsupporting
confidence: 85%
“…In Group C, the success rate results to be higher if compared with the already published data ranging from 83.3 to 88.2% 27 with a considerably lower early and long-term postoperative complications rate. 19 28 29 30 31 …”
Section: Discussionmentioning
confidence: 99%
“…Following the introduction by Longo in 1998 of the transanal stapled procedure for hemorrhoids, 18 our group and others have translated variants of this technology to patients with obstructed defecation syndrome and related prolapse disorders, 19-21 establishing the feasibility and safety of the use of a larger housing afforded by the tissue-selecting technique (TST) stapler. 9,22 At 36 mm, the large-diameter casing of the stapler permits a greater volume of resection 7 with improved removal of prolapsed tissue under improved visualization during instrumental closure.…”
Section: Discussionmentioning
confidence: 99%
“…They argue that the resection of the muscular layer in the STARR procedure is not adequate to strengthen the anterior rectal wall; thus, recurrence can be expected in the future. Some supporters of the STARR procedure also admitted that, so several modified STARR procedures were invented[34,35] to ensure the effectiveness of anterior wall repair. However, none of these modified procedures has been accepted as a gold-standard procedure as the long-term curative effect is not clear.…”
Section: Discussionmentioning
confidence: 99%